2013
DOI: 10.1007/s00401-013-1192-8
|View full text |Cite
|
Sign up to set email alerts
|

Antisense transcripts of the expanded C9ORF72 hexanucleotide repeat form nuclear RNA foci and undergo repeat-associated non-ATG translation in c9FTD/ALS

Abstract: Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) are devastating neurodegenerative disorders with clinical, genetic, and neuropathological overlap. A hexanucleotide (GGGGCC) repeat expansion in a non-coding region of C9ORF72 is the major genetic cause of both diseases. The mechanisms by which this repeat expansion causes “c9FTD/ALS” are not definitively known, but RNA-mediated toxicity is a likely culprit. RNA transcripts of the expanded GGGGCC repeat form nuclear foci in c9FTD/ALS, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
604
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 537 publications
(622 citation statements)
references
References 40 publications
16
604
2
Order By: Relevance
“…Dipeptide repeat protein and TDP-43 inclusion formation was assessed using immunohistochemistry with the following antibodies: TDP-43 (anti-rabbit, 1:2500, Proteintech), phospho-TDP-43 (pTDP-43, anti-rat, 1:500, courtesy of Prof. Manuela Neumann, University Hospital Tü bingen, Germany), and dipeptide repeat protein antibodies, developed by one of the authors (L.P.), that recognize GA (anti-rabbit, 1:20 000), GP (Gly-Pro) (anti-rabbit, 1:20 000), GR (Gly-Arg) (anti-rabbit, 1:5000), PA (Pro-Ala) (anti-rabbit, 1:5000) and PR (Pro-Arg) (anti-rabbit, 1:2000) Gendron et al, 2013). Immunostained sections were counterstained with Harris haematoxylin.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Dipeptide repeat protein and TDP-43 inclusion formation was assessed using immunohistochemistry with the following antibodies: TDP-43 (anti-rabbit, 1:2500, Proteintech), phospho-TDP-43 (pTDP-43, anti-rat, 1:500, courtesy of Prof. Manuela Neumann, University Hospital Tü bingen, Germany), and dipeptide repeat protein antibodies, developed by one of the authors (L.P.), that recognize GA (anti-rabbit, 1:20 000), GP (Gly-Pro) (anti-rabbit, 1:20 000), GR (Gly-Arg) (anti-rabbit, 1:5000), PA (Pro-Ala) (anti-rabbit, 1:5000) and PR (Pro-Arg) (anti-rabbit, 1:2000) Gendron et al, 2013). Immunostained sections were counterstained with Harris haematoxylin.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…These candidates include loss of C9orf72 gene product function and toxicity through repeat RNA foci and protein aggregation. RNA foci can be composed of sense or antisense repeat mRNA strands (DeJesus-Hernandez et al, 2011;Gendron et al, 2013;Mizielinska et al, 2013) and have been shown to sequester RNA-binding proteins, leading to transcriptome abnormalities (Donnelly et al, 2013;Lee et al, 2013;Mori et al, 2013a;Sareen et al, 2013). Expanded repeats also undergo abnormal repeat associated non-ATG (RAN) translation (Zu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, at present we have three plausible, and indeed not mutually exclusive, hypotheses for neurotoxicity: in fact studies have shown that cells accumulating toxic RNA foci again do not overlap with those accumulating DPRs [21,43], suggesting these are complimentary and not competing events. So where does this leave us?…”
mentioning
confidence: 80%
“…This too occurs in C9ALS and C9FTLD with translation of the expansion occurring in both a sense and an antisense direction, leading to the formation and brain aggregation of all five possible dipeptide repeat proteins (DPRs) [3,21,45,47,67,69]. Indeed, DPR can consist of any or all of the five possible species [3,21,39,40,45,47,67,69].…”
mentioning
confidence: 99%
See 1 more Smart Citation